MAFF mitigates oxidative stress and pyroptosis in cardiopulmonary bypass-induced myocardium injury - Yuan, Lei; Wang, Duo; Su, Yale; Yuan, Long; Li, Mixia; Zheng, Dongdong; Zhu, Cuilin; Piao, Hulin; Wang, Yong; Zhu, Zhicheng; Li, Dan; Wang, Tiance; et al. (Frontiers in Physiology, 2025)
BackgroundCardiopulmonary bypass (CPB) remains an indispensable technique for open-heart surgery; however, it induces systemic inflammation and oxidative stress, leading to myocardial cell damage and compromised prognosis. Optimizing myocardial protection during CPB remains a critical objective. This study aimed to identify potential therapeutic targets for myocardial protection during CPB.MethodsWe performed weighted gene co-expression network analysis (WGCNA) on previously published datasets (GSE12486, GSE132176, GSE14956, and GSE38177) to identify CPB-related hub genes. An in vitro model of oxidative stress was established using H2O2-treated H9C2 cardiomyocytes to validate these hub genes. Through systematic validation, we identified the most representative hub gene. Subsequent functional studies, including gene knockdown and overexpression experiments, were conducted to elucidate its role and underlying mechanisms in oxidative stress-induced cardiomyocyte injury.ResultsIntegrated bioinformatics analysis and experimental validation identified MAFF as the most differentially expressed hub gene between pre- and post-CPB conditions. In the oxidative stress model, MAFF overexpression demonstrated cardioprotective effects by maintaining cell viability, significantly reducing reactive oxygen species (ROS) accumulation in both cytoplasm and mitochondria, and attenuating pyroptosis-mediated cell death.ConclusionOur findings demonstrate that MAFF exerts protective effects against oxidative stress-induced cardiomyocyte injury, positioning it as a promising therapeutic target for myocardial protection. These results provide novel insights into optimizing postoperative recovery and improving clinical outcomes for patients undergoing CPB-assisted cardiac surgery.